ALAT PEMANTAU KUALITAS UDARA BERBASIS IOT - Sulistyo, Eko; Alfarizi, Muhammad Abdurahman; Tiara Yasmin Arimbi Chantika; Andik Setiawan, I Made (Prosiding Seminar Nasional Inovasi Teknologi Terapan, 2024)
Some of the main causes of respiratory and cardiovascular diseases are due to bad air pollution. Not all areas have SPKUAs, such as Sungailiat, Bangka Belitung. Areas with worse air pollution are prioritized for SPKUA installation. In addition, cost and complex installation factors are barriers to SPKUA distribution. To overcome these problems, this research developed an air quality monitoring device IoT-based that is more efficient, easy to use, portable and IoT-based. This research aims to create an IoT-based air quality monitoring device using ESP32, MQ sensor, DHT22 sensor and dust sensor. The process includes designing, and creating an air quality monitoring program, designing electrical and hardware then making and integrating software and hardware, and testing the air quality monitoring device. That this IoT-based air quality monitoring device can detect and measure important factors for air quality. Overall, the goal of this project to provide an efficient and effective air quality monitoring solution has been achieved. The system can provide real-time air condition information, which is highly beneficial for environmental, health, and public safety purposes.